Modulation of NK cell activation by exogenous calcium from alginate dressings in vitro - Adib, Yara; Boy, Maxime; Serror, Kevin; Dulphy, Nicolas; des Courtils, Céline; Duciel, Laura; Boccara, David; Mimoun, Maurice; Samardzic, Marina; Bagot, Martine; Bensussan, Armand; Michel, Laurence (Frontiers in Immunology, 2023)
Natural Killer (NK) cells participate in the defense against infection by killing pathogens and infected cells and by secreting immuno-modulatory cytokines. Defects in NK cell activity have been reported in obese, diabetic, and elderly patients that are at high risk of developing infected chronic wounds. Calcium alginate dressings are indicated for the debridement during the inflammatory phase of healing. Since calcium ions are major activators of NK cells, we hypothesized that these dressings could enhance NK functions, as investigated in vitro herein. Primary human blood NK cells were freshly-isolated from healthy volunteers and exposed to conditioned media (CM) from two alginate dressings, Algosteril® (ALG, pure Ca2+ alginate) and Biatain® Alginate (BIA, Ca2+ alginate with CMC), in comparison with an exogenous 3mM calcium solution. Our results demonstrated that exogenous calcium and ALG-CM, but not BIA-CM, induced NK cell activation and enhanced their capacity to kill their targets as a result of increased degranulation. NK cell stimulation by ALG depended on the influx of extracellular Ca2+ via the SOCE Ca2+ permeable plasma membrane channels. ALG-CM also activated NK cell cytokine production of IFN-γ and TNF- through a partly Ca2+ independent mechanism. This work highlights the non-equivalence between alginate dressings for NK cell stimulation and shows that the pure calcium alginate dressing Algosteril® enhances NK cell cytotoxic and immuno-modulatory activities. Altogether, these results underline a specific property of this medical device in innate defense that is key for the cutaneous wound healing process.